Pemodelan Perambatan Gelombang Mixed Rossby-Gravity di Lapisan Stratosfer Bawah Menggunakan Algoritma Linier Gauss-Newton - Rizkia Putri Syafina; Noersomadi Noersomadi; Dasep Dasep (Jurnal EurekaMatika, 2022)
The energy transfer process transported by equatorial atmospheric waves has a potential effect on climate change issues. For detecting wave propagation, an analysis of the vertical atmospheric profile could be obtained from radiosonde balloon observations. This study aims to apply the Gauss-Newton linear algorithm model on the temperature (T) and the northward wind component (v) variables in the lower stratosphere, the layer around the altitude of 21 km above sea level. Fluctuations of T and v triggered a non-linear problem in determining the wave parameters, including amplitude and phase. These two parameters are examined using a non-linear inversion method with a linear Gauss-Newton approximation. The results showed that fluctuations in T and v of the model and observation data coincide with the value range -4.5 to 4.5 K (cold-warm) and -15 to 15 m/s (southward-northward wind). There is a movement in T fluctuations to the westward in the period of 13–24 April 2021. Likewise, a similar movement in v fluctuations was indicated during 13–22 May 2021. The westward propagation represented the propagation of the Mixed Rossby-gravity wave.Keywords: Atmospheric Waves, Gauss-Newton Linear Method, Northward Wind Component, Temperature.AbstrakProses transfer energi yang dibawa gelombang atmosfer ekuatorial berpotensi mempengaruhi isu perubahan iklim. Untuk mendeteksi perambatan gelombang dapat dilakukan analisis data vertikal atmosfer dari pengamatan balon radiosonde. Penelitian ini bertujuan menerapkan model algoritma linier Gauss-Newton terhadap variabel temperatur (T) dan komponen angin utara-selatan (v) di lapisan stratosfer bawah atau ketinggian 21 km di atas permukaan laut. Fluktuasi T dan v memunculkan masalah non-linier dalam pencarian parameter gelombang berupa amplitudo dan fasa. Kedua parameter tersebut dicari menggunakan metode inversi non-linier dengan pendekatan linier Gauss-Newton. Hasil penerapan model menunjukkan nilai yang berhimpit pada fluktuasi T dan v dengan rentang nilai –4,5 hingga 4,5 K (dingin-hangat) dan –15 sampai 15 m/s (arah angin menuju selatan-utara). Untuk variabel T, terlihat adanya pergerakan menuju ke arah barat pada rentang waktu 13–24 April 2021, demikian pula pada variabel v terdeteksi pergerakan ke arah yang sama untuk rentang waktu 13–22 Mei 2021. Perambatan gelombang ke arah barat ini merepresentasikan penjalaran gelombang Mixed Rossby-Gravity.